Advancements in electrical systems for E-bike battery charging: a technical examination of conventional and wireless power transfer technologies - Bunyamin, Wan Muhamad Hakimi Wan; Baharom, Rahimi; Munim, Wan Noraishah Wan Abdul; Zolkiffly, Mohd Zaid; Ahmad, Ahmad Sukri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Electric bicycles (E-bikes) are becoming key to making transportation more eco-friendly, leading to cleaner air, and lower carbon emissions. The rising popularity of E-bikes calls for innovative battery charging solutions that cater to their specific needs, emphasizing faster charging, high energy efficiency, safety, compact design, smart features, and compliance with international standards. This paper reviews existing and new charging technologies for E-bikes, focusing on their design, charging processes, and safety features. It points out the issues with traditional chargers, such as their negative effects on power quality and grid stability, and introduces wireless power transfer (WPT) as a groundbreaking approach to E-bike charging. WPT enhances convenience by removing the need for physical cables and is seen as a step forward with the integration of power factor correction techniques for better efficiency and energy use. The discussion extends to the future of E-bike charging, exploring emerging technologies that could redefine electric transportation. The study aims to deepen the understanding of E-bike battery charging technologies, their challenges, and future directions, contributing to the advancement of E-bike technology.